The development and maintenance of mental toughness: Perceptions of elite performers - Connaughton, D.; Wadey, R.; Hanton, S.; Jones, G. (Journal of Sports Sciences, 2008)
Seven participants from a previous study (Jones, Hanton, & Connaughton, 2002) agreed to be interviewed about the development of mental toughness. We also aimed to determine whether mental toughness requires maintenance. Semi-structured interviews were conducted to elicit the participants' perceptions of how mental toughness is cultivated and retained. Findings indicated that the development of mental toughness is a long-term process that encompasses a multitude of underlying mechanisms that operate in a combined, rather than independent, fashion. In general, these perceived underlying mechanisms related to many features associated with a motivational climate (e.g. enjoyment, mastery), various individuals (i.e. coaches, peers, parents, grandparents, siblings, senior athletes, sport psychologists, team-mates), experiences in and outside sport, psychological skills and strategies, and an insatiable desire and internalized motives to succeed. It was also reported that once mental toughness had been developed, three perceived underlying mechanisms were required to maintain this construct: a desire and motivation to succeed that was insatiable and internalized, a support network that included sporting and non-sporting personnel, and effective use of basic and advanced psychological skills. Practical implications and future avenues of research are discussed.